Impact of extreme weather events on agricultural production and household livelihoods in rural Malawi - Mukete Beckline; Ngoe Mukete; Tahle Mukete (Academia Environmental Sciences and Sustainability)
Due to the high dependence of Malawians on rain-fed agriculture, frequent extreme weather events expose their rural farming households to droughts, floods, low agricultural production, and food insecurity. This study used fixed-effects regressions and panel data from the Malawi Integrated Household Panel Surveys (2010–2017) to assess the impact of extreme weather events on maize yield and value of agricultural output. Furthermore, the study adopted a Probit model to analyze the determinants of the households’ choice of coping strategies. Using drought shock as an indicator for extreme weather events, results showed that 1% increase in the exposure to drought decreased the maize yield by 12.6% and the value of agricultural output by 24.1%. The results from the Probit analysis indicated that the age of the household head, level of education, increase in the dependency ratio, and access to extension services were the different determinants of the households’ choice of coping strategies. Undertaking ganyu labor, receiving remittances, obtaining credit, selling household assets, and relying on own savings were the coping and effective coping strategies employed by households to offset potential income loss. The study recommends the implementation of income diversification activities, application of irrigation systems, improvement in livestock production, and increase in access to rural credit in order to improve household capacity to cope with extreme weather events.